Payout Policy Trade-Offs and the Rise of 10b5-1 Preset Repurchase Plans - Bonaimé, Alice; Harford, Jarrad; Moore, David (Management Science, 2020)
We are the first to document and study the use of Rule 10b5-1 preset repurchase plans. Though the rule’s original intent was to clarify conditions for enforcing insider trading laws, generally thought to apply to individuals classified as firm insiders, we find strong use of the rule at the firm level to repurchase company stock. We exploit this new and widespread form of payout to examine an issue at the core of payout decisions—the trade-off between commitment and financial flexibility. Relative to open market repurchases, preset plans provide an expanded repurchase window and increased legal cover, albeit at the cost of reducing repurchase flexibility and the option to time repurchases. These costs and benefits are significantly associated with Rule 10b5-1 adoption: Firms with alternative sources of financial flexibility are more likely to precommit to a repurchase plan, as are firms with a history of poor repurchase timing and firms constrained by blackout windows. Consistent with preset plans signaling commitment, Rule 10b5-1 repurchase announcements are associated with greater and faster completion rates, with more positive market reactions, and with more dividend substitution than open market repurchases. Lastly, we find that preset repurchase plans represent a unique payout tool whose introduction encouraged a different set of firms to buy back stock and significantly altered the payout landscape. This paper was accepted by David Simchi-Levi, Finance.